Diffusion tensor imaging analysis of the brain in the canine model of Krabbe disease. Issue 6 (December 2016) - Bradbury, Allison; Peterson, David; Vite, Charles; Chen, Steven; Ellinwood, N Matthew; Provenzale, James
Purpose: The goal of this study was to compare the diffusion tensor imaging (DTI) metrics from an end-stage canine Krabbe brain evaluated by MR imaging ex vivo to those of a normal dog brain. We hypothesized that the white matter of the canine Krabbe brain would show decreased fractional anisotropy (FA) values and increased apparent diffusion coefficient (ADC) and radial diffusivity (RD) values. Methods: An 11-week-old Krabbe dog was euthanized after disease progression. The brain was removed and was placed in a solution of 10% formalin. MR imaging was performed and compared to the brain images of a normal dog that was similarly fixed post-mortem. Both brains were scanned using similar protocols on a 7 T small-animal MRI system. For each brain, maps of ADC, FA, and RD were calculated for 11 white-matter regions and five control gray-matter regions. Results: Large decreases in FA values, increases in ADC values, and increases in RD (consistent with demyelination) values, were seen in white matter of the Krabbe brain but not gray matter. ADC values in gray matter of the Krabbe brain were decreased by approximately 29% but increased by approximately 3.6% in white matter of the Krabbe brain. FA values in gray matter were decreased by approximately 3.3% but decreased by approximately 29% in white matter. RD values were decreased by approximately 27.2% in gray matter but increased by approximately 20% in white matter. Conclusion: We found substantial abnormalities of FA, ADC, and RD values in an ex vivo canine Krabbe brain.